Assessing and treating sexual offenders with mental disorders. Issue 2 (6th May 2014) - Lord, Alex; Perkins, Derek
Abstract : Purpose: – The purpose of this paper is to increase our understanding of the role of mental disorder in sexual offending as well as identifying innovations in assessment and treatment with offenders who present with these typically complex risks and needs. Design/methodology/approach: – The converging literatures on "good lives" and other developments in sexual offender treatment are compared with recovery from mental disorder and what is known about the particular needs and characteristics of sexual offenders with mental illness and severe personality disorder (PD). Findings: – A key outcome of this review is that many mentally disordered sexual offenders have similar needs to those in prison and the community but there are particular challenges posed by severe PD, paraphilias and the relatively rare individuals whose offending is functionally linked to psychotic symptoms. Practical implications: – Practical implications include the need for case formulation of complex needs related to mental disorder using direct and indirect measures of attitudes and interests. Treatment needs to be responsive to very different personality and mental health presentations as well as problems with offending and cognitive schemas. Direct functional links between mental health symptoms such as delusions and hallucinations are very rare in practice and are usually secondary to PD and sexual offending issues. In practice, treatment promoting recovery from mental disorder is highly compatible with the "good lives" approach to sexual offender treatment. Staff development, supervision and support are particularly important for staff treating mentally disordered sexual offenders. Originality/value: – It is argued that mentally disordered sexual offenders are an under-researched sub-group within the wider sexual offender population. This paper brings together the relatively limited literature on treatment with examples of recent treatment innovations, multi-modal assessment approaches and reviews of research on the needs of this relatively uncommon but highly risky group.